Clinical and genetic analysis for two children with congenital disturbance of glycosylation with PMM2 gene mutations - Ren, Changhong (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2015)
OBJECTIVE: To analyze the clinical and PMM2 gene mutation features of congenital disturbance of glycosylation caused by PMM2 gene mutation (PMM2-CDG, previously known as CDG 1a)